Sustainable Consumerism: Green-Purchasing Trends among Generation Z - Ashmita Dahal Chhetri; Pawan Poudel (Journal of Development and Administrative Studies, 2024)
This research investigates the perceptions surrounding green products and identifies key factors influencing green purchasing behavior. The primary objective is to understand the determinants that drive Generation Z's green purchasing decisions in the Chitwan district. A causal-comparative research design was employed to explore the relationships between variables affecting green purchasing behavior. Data were gathered from 189 participants through structured questionnaires, using a purposive sampling technique. Quantitative analyses, including both descriptive and inferential statistics, were conducted, with the PLS-SEM method utilized for evaluating the proposed model. The study reveals that factors such as environmental knowledge, governmental initiatives, and social influences significantly impact green purchasing decisions among Generation Z. Conversely, environmental attitudes and the sense of environmental responsibility do not demonstrate a significant influence on their purchasing behavior. This study is limited to Generation Z within the Chitwan district and relies on cross-sectional data, which may restrict the applicability of its findings to other contexts. Future research should consider examining determinants of green purchasing behavior across different demographic groups and geographic regions. Despite these constraints, the study provides meaningful insights for various stakeholders, including policymakers, businesses, and marketers. The findings offer practical guidance for businesses, marketing professionals, and policymakers to design strategies and products that align with Generation Z's inclination toward green products. Additionally, the outcomes encourage the development of initiatives that foster sustainable consumption habits, thereby supporting environmental preservation efforts within the Chitwan district.